The financial performance: a case study of Tenaga Nasional Berhad / Abdul Halim Abu Bakar - Abu Bakar, Abdul Halim (Faculty of Business and Management, 2010)
Tenaga Nasional Berhad is the only utilities company which generates, transmits, and distributes electricity through out Peninsular Malaysia. TNB transmits the energy through its National Grid. After six decades of operation, TNB had been recognized around the globe. TNB shows an amazing performance through its financial statement. However, for the past 2 years TNB performance declined. This is may be due to the economic crisis and the increasing of the coal and oil price. As a result, the total operating expenses for TNB had been increased and therefore its total net income decreased. This report had been done to evaluate the performance of TNB. Both primary data and secondary data had been collected. Face to face interviews had been done to get more information related to the issues. Five financial year of TNB had been compared as to evaluate the performance. From the data, researcher found that starting from the year 2008, net income for the company had declined due to increasing in total operating expenses. From the tools and measurement of analysis that had been used, the company still can managed its cash and generates in high revenue for the years. Other than that, the objective of this study is to identify the gap. From the results, its shows the different method used by the company compared to the past researcher in Debt to Equity Ratio and Return on Assets. Therefore, some suggestions issued. TNB should focus more on its debts as most of their assets are finance by debts. Other than that, the biomass project should be continue in order for the company to replace the used of coal, gas and oil. Study should be done more on nuclear technology as this will help TNB boosting their performance.